Heme Oxygenase, Inflammation, and Fibrosis: The Good, the Bad, and the Ugly? - Lundvig, Ditte M.; Immenschuh, Stephan; Wagener, Frank A. (Frontiers in Pharmacology, 2012)
Upon injury, prolonged inflammation and oxidative stress may cause pathological wound healing and fibrosis, leading to formation of excessive scar tissue. Fibrogenesis can occur in most organs and tissues and may ultimately lead to organ dysfunction and failure. The underlying mechanisms of pathological wound healing still remains unclear, but are considered to have a multifactoral pathogenesis, and so far, no efficient anti-fibrotic therapies exists. Extra- and intracellular levels of free heme may be increased in a variety of pathological conditions due to heme-release from hemoproteins. Free heme possesses pro-inflammatory and oxidative effects, and may act as a danger signal, which counteracted by protein scavenging via various heme-binding proteins and by heme degradation. Heme is degraded by heme oxygenase (HO) that exists as two isoforms: inducible HO-1 and constitutively expressed HO-2. This generates the effector molecules biliverdin, carbon monoxide, and free iron. HO deficiency in mouse and man leads to exaggerated inflammation upon insults, and still accumulating epidemiological and preclinical studies support the widely recognized notion of the cytoprotective, anti-oxidative, and anti-inflammatory effects of the activity of the HO system and the generated effector molecules. In this review, we address the potential applications of targeted HO-1 induction or administration of its effector molecules as therapeutic targets in fibrotic and inflammatory conditions to counteract inflammatory and oxidative insults. This is shown in various clinically relevant conditions, such as hypertrophic scarring, chronic inflammatory liver disease, chronic pancreatitis, and chronic graft rejection in transplantation.